Sales Promotion sebagai Strategi Komunikasi Pemasaran dalam Meningkatkan Penjualan pada Produk Indihome - Caroline Caroline (VISA: Journal of Vision and Ideas, 2023)
The purpose of this study is to determine the marketing communication strategy in the development of PT Telkom's product sales, namely IndiHome. This study uses descriptive qualitative research methods, with documentary data collection techniques. The results of the study show that there is the use of the STOP-SIT marketing communication strategy in the marketing communication strategy in Sales Promotion to increase sales, namely Segmentation, Targeting, Objectives, Positioning, Sequence of Tools, Integrating, Tools. In the marketing communication strategy in sales promotion to increase sales, studies continue to be carried out to find out the strengths and weaknesses of selling IndiHome products, identify all opportunities and obstacles or threats faced. Marketing promotion or development programs are prepared by considering various aspects, and analyzing the specified market, namely potential consumers/customers of IndiHome products. In the STOP-SIT analysis, you should also know the problems or obstacles or strengths owned by the company. Keywords: Marketing communication strategy, sales promotion, IndiHome